The Musical Harmony of The Cosmos and The Soul After Pytagoras - Yardi, Apri; Munthe, Yesyurun; Letnora, Chris; Sihombing, Octa Maria (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The writing begins with a literature review as part of the research method on musical harmonisation. Music harmonisation is a diverse field with varying definitions, including those from music, anthropology, culture, and economics. It focuses on the philosopher Pythagoras' thoughts on music as a materialist instrument. The research method employs a qualitative approach and gathers data from secondary sources, specifically previous research. The findings indicate that Pythagorean-based music harmonisation demonstrates music as an organised rhythm, melody, and harmony, similar to the harmonisation of the structured and mathematically diverse cosmos or universe..